Adrodd ar Dlodi Naratif y Cyfryngau Newyddion a Chyfathrebiadau'r Trydydd Sector yng Nghymru - Moore, Kerry (Cardiff University Press, 2020)
This book presents a detailed and systematic investigation of poverty reporting in Wales, discussing the findings of a two-year research project funded by Exploring the Narrative Coalition (a group of 10 third sector organizations based in Wales ESRC and Cardiff University Exploring how poverty news is covered by broadcast, print and online news in English and Welsh, provides a detailed understanding of current journalism and communication practices on a critical issue. facing Wales. Following a decade of austerity policies, with official measures confirming that experiences of poverty and deprivation are on the rise, the book offers a timely intervention, critically exploring the mainstream media's narratives on poverty and how they experience it shape them. This book is based on original research conducted between 2016-7, during a turbulent period involving the Tata Steel crisis in Port Talbot. South Wales, Welsh Government elections and a referendum campaign for the UK's membership of the European Union. It covers how poverty was framed in the midst of nationally important news about politics, business and the economy as well as more local, personal or community-related stories about livelihoods and social issues. Quantitative analysis of the key features of the approaches across different media types provides a detailed evidence base for understanding how poverty news was represented. This includes looking at the major contextualization themes, social groups and geographical locations that are commonly addressed, the causes and consequences of poverty, and access to information. It demonstrates how the media in Wales responds differently to the more negative reports typical of some UK national press departments, particularly around discourses that cause unemployment and welfare stigma. Nevertheless, there are important questions to be raised about how news narratives convey meaning and in particular the disconnect between the coverage of macroeconomic trends or events and their impact on the lives of ordinary people. In addition, the book explores why coverage of poverty news is shaped as it is, drawing on the findings of in-depth interviews with journalists and editors about their practices. Through a look at professional values ​​and experiences, the book explores the challenges that are likely to affect reporting poverty. Key issues include the use of specialist resources and expertise allocated to social issues journalism, the difficulties in identifying and potentially reaching vulnerable groups across Wales and representing case studies fairly and ethically. We undertook a set of interviews with third sector professionals about their engagement with news media practices and contacts. They offer more information on how news about poverty is shaped. Here, the pressures of reporting poverty are viewed from a different perspective, where trying to influence poverty coverage in the press and responding to news demands can create professional tensions between journalists and the third sector and / or positive productive co-operative relationships that affect news narratives. By providing a detailed picture of how and why poverty news narratives are shaped as they are, the book intends to create an evidence base that will inform more accurate, representative and meaningful reporting of poverty in Wales.